Virucidal Action Mechanism of Alcohol and Divalent Cations Against Human Adenovirus - Martín-González, Natalia; Vieira Gonçalves, Leonam; Condezo, Gabriela N.; San Martín, Carmen; Rubiano, María; Fallis, Ian; Rubino, Joseph R.; Ijaz, M. Khalid; Maillard, Jean-Yves; De Pablo, Pedro J. (Frontiers in Molecular Biosciences, 2020)
Hygiene and disinfection practices play an important role at preventing spread of viral infections in household, industrial and clinical settings. Although formulations based on >70% ethanol are virucidal, there is a currently a need to reformulate products with much lower alcohol concentrations. It has been reported that zinc can increase the virucidal activity of alcohols, although the reasons for such potentiation is unclear. One approach in developing virucidal formulations is to understand the mechanisms of action of active ingredients and formulation excipients. Here, we investigated the virucidal activity of alcohol (40% w/v) and zinc sulfate (0.1% w/v) combinations and their impact on a human adenovirus (HAdV) using, nucleic acid integrity assays, atomic force microscopy (AFM) and transmission electron microscopy (TEM). We observed no difference in virucidal activity (5 log10 reduction in 60 min) against between an ethanol only based formulation and a formulation combining ethanol and zinc salt. Furthermore, TEM imaging showed that the ethanol only formulation produced gross capsid damage, whilst zinc-based formulation or formulation combining both ethanol and zinc did not affect HAdV DNA. Unexpectedly, the addition of nickel salt (5 mM NiCl2) to the ethanol-zinc formulation contributed to a weakening of the capsid and alteration of the capsid mechanics exemplified by AFM imaging, together with structural capsid damage. The addition of zinc sulfate to the ethanol formulation did not add the formulation efficacy, but the unexpected mechanistic synergy between NiCl2 and the ethanol formulation opens an interesting perspective for the possible potentiation of an alcohol-based formulation. Furthermore, we show that AFM can be an important tool for understanding the mechanistic impact of virucidal formulation.